DEVELOPMENT OF A PROBLEM-BASED LEARNING-BASED MATHEMATICS E-MODULE USING FLIPBOOK MAKER ON NUMBER PATTERN MATERIAL - Fadila Taulanita Arif; Ira Vahlia; Sudarman Dami (EMTEKA: Jurnal Pendidikan Matematika, 2026)
This research is based on the problem found at SMPN 2 Batanghari through interviews and observations, lack of interest in students in understanding mathematical concepts and the importance of utilizing existing technology. Learning is only spurred by print media while the existing technological facilities and infrastructure are adequate such as tabs and Wi-Fi networks that can be used by students. The purpose of this research is to develop a Math E-Module learning media with the Problem Based Learning model and with the help of Flipbook Maker in the number pattern material. This E-Module is designed to contain a summary of the material, sample questions and qr code that is linked to the learning video. This research model uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The results of this study in the form of a learning media for a Mathematical E-Module with a Problem Based Learning model and the help of a Flipbook Maker on the number pattern material developed with validation results and practicality tests. The material validation results obtained with an average presentation of 85% included in the very valid category, and the media validation results obtained with an average presentation of 91% included in the very valid category. It can be concluded that E-Module Mathematics with the Problem Based Learning model and the help of Flipbook Maker in the number pattern material is very valid and very practical.